Sajiyä islam bilimliri tori (2016)
Hierbei werden das Ziel, die Aufgabengebiete dieser Webseite und die Biographie und die Forschungsschwerpunkte des Autors dieser Webseite beschrieben. - This includes a description of the objective, the tasks of this website and the biography and research focus of the author of this website.